"The Fight is Two Times as Hard": A Qualitative Examination of a Violence Syndemic Among Young Black Sexual Minority Men. Issue 13 (July 2023) - Quinn, Katherine G.; Edwards, Travonne; Johnson, Anthony; Spector, Antoinette; Takahashi, Lois; Dakin, Andrea; Bouacha, Nora; Valadez-Tapia, Silvia; Voisin, Dexter
Young Black men who have sex with men (YBMSM) are disproportionately impacted by violence, including violence rooted in anti-Black racism, sexual identity bullying, and neighborhood violence rooted in structural racism and inequities. These multiple forms of violence are frequently co-occurring and interactive creating syndemic conditions that can negatively impact HIV care. This qualitative study is based on in-depth interviews with 31 YBMSM, aged 16–30 years, living with HIV in Chicago, IL, to examine how violence has impacted their lives. Using thematic analysis, we identified five themes that reflect how YBMSM experience violence at the intersection of racism, homonegativity, socioeconomic status, and HIV status: (a) the experience of intersectional violence; (b) long histories of violence contributed to hypervigilance, lack of safety, and lack of trust; (c) making meaning of violence and the importance of strength; (d) normalizing violence for survival; and (e) the cyclical nature of violence. Our study highlights how multiple forms of violence can accumulate across an individual's life and contribute to social and contextual situations that further contribute to violence and negatively impact mental health and HIV care.